Pharmacokinetic study of ofloxacin enantiomers in Pagrosomus major by chiral HPLC. (27th August 2015) - Nie, Jing; Wang, Yang–Guang; Gao, Xiao–Feng; OuYang, Xiao–kun; Yang, Li–Ye; Yu, Di; Wu, Wei–jian; Xu, Hong–Ping
Abstract: ( S )‐(−)‐Ofloxacin and ( R )‐(+)‐ofloxacin concentrations in the plasma of Pagrosomus major after drug treatment were detected by chiral high‐performance liquid chromatography, and various pharmacokinetic parameters were calculated from these data. The elimination half‐life of ( S )‐(−)‐ofloxacin was significantly shorter than that of the ( R )‐(+) enantiomer. ( S )‐(−)‐Ofloxacin also had a significantly lower maximum plasma concentration, area under the concentration–time curve from zero to infinity, and mean residence time than ( R )‐(+)‐ofloxacin. However, the apparent volume of distribution and total body clearance of ( S )‐(−)‐ofloxacin were greater than those of ( R )‐(+)‐ofloxacin. The ratio of the ( S )‐(−)‐ to ( R )‐(+)‐ofloxacin plasma concentration was always <1.0. Together, these data suggest that ( S )‐(−)‐ofloxacin was preferentially excreted and ( R )‐(+)‐ofloxacin was preferentially absorbed. Although the difference in pharmacokinetic parameters was small, the metabolic behavior of the ofloxacin enantiomers in P. major was enantioselective. Copyright © 2015 John Wiley & Sons, Ltd.